2010
DOI: 10.1063/1.3352892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe doping and the dielectric constant on the room temperature ferromagnetism of polycrystalline CeO2 oxides

Abstract: Impact of sintering temperature on the physical properties of the superconducting ferromagnet: Ru Sr 2 Eu 1.5 Ce 0.5 Cu 2 O 10 Ce 1−x Fe x O 2−␦ polycrystalline samples with x = 0% -8% were synthesized by the solid phase reaction method at a low sintering temperature of 1250°C, and the effect of Fe content on the magnetic behaviors has been systemically investigated. It is found that the pure CeO 2 samples are diamagnetic, while doped samples unambiguously show the existence of room temperature ͑RT͒ ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Recently, Coey et al proposed a model to explain the observed ferromagnetism, based on impurity-band exchange and density-functional calculations by considering the oxygen-defect-induced donor sites. In the F-center-mediated mechanism, the radius of the electron orbital is a direct function of the dielectric constant . Since CeO 2 has a high dielectric constant of 26, the radius of the F-center electrons may be large enough to produce magnetic interactions at low Co concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Coey et al proposed a model to explain the observed ferromagnetism, based on impurity-band exchange and density-functional calculations by considering the oxygen-defect-induced donor sites. In the F-center-mediated mechanism, the radius of the electron orbital is a direct function of the dielectric constant . Since CeO 2 has a high dielectric constant of 26, the radius of the F-center electrons may be large enough to produce magnetic interactions at low Co concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In the F-center-mediated mechanism, the radius of the electron orbital is a direct function of the dielectric constant. 35 Since CeO 2 has a high dielectric constant of 26, the radius of the F-center electrons may be large enough to produce magnetic interactions at low Co concentrations. As x increases to 0.04, a fraction of the Co ions are likely to enter the interstitial positions which require an excess of oxygen ions for charge neutrality.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…fact that Fe doping into CeO 2 matrix lead to enhanced level of oxygen vacancies which will lead to more exchange integrations with Ce 3+ and enhanced magnetization [25,26]. Moreover, the doped Fe 3+ ions can also lead to enhanced magnetic characteristics via same exchange interaction (i.e.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…The anti-oxidative properties of cerium oxides are attributed to the coexistence of Ce 3+ and Ce 4+ oxidative states of the cerium atom, which is is controlled by oxygen deficiencies. Even though the electronic structure of cerium oxides is relatively poor in electrons (compared to other rare and transition metal oxides), there have been reports of room temperature magnetism in these materials [12][13][14][15][16][17][18][19]. For a more comprehensive list, please see [20] and references therein.…”
Section: Introductionmentioning
confidence: 99%